Characteristics and Outcomes of Acetaminophen Overdose and Hepatotoxicity in Thailand - Pholmoo, Natthiya (J Clin Transl Hepatol, 2019)
Background and Aims: Acetaminophen (APAP) is the leading cause of drug overdose and hepatotoxicity worldwide, including in Thailand. Patterns of overdose and hospital management are known to have significant impacts on the outcomes of APAP overdose, and these factors vary from country to country. Therefore, this study aimed to analyze clinical characteristics of Thai patients with APAP overdose in terms of overdose patterns, clinical presentation, treatment and outcomes. Methods: In this retrospective analytical study, medical records of adult patients hospitalized with a diagnosis of APAP overdose at Rajavithi Hospital, Bangkok, between January 2013 and December 2017 were reviewed. Results: A total of 184 patients diagnosed with APAP overdose were included. The median age was 22 (15–76) years and the majority were female (79.9%). Most overdoses were intended self-poisoning ingestion (90.8%) with a median dose of 10.5 g (4.5–50). A total of 121 patients were treated with N-acetylcysteine with a median visit-to-N-acetylcysteine time of 2 (0.5–15) h. Overall, 15.6% developed mild hepatotoxicity (aspartate aminotransferase or alanine aminotransferase >3 times the upper limit of normal), 6.4% developed severe hepatotoxicity (aspartate aminotransferase or alanine aminotransferase >10 times the upper limit of normal and international normalized ratio >2.0) and 3 patients developed acute liver failure (1 patient resolved spontaneously and 2 patients, neither of whom had a liver transplant, died). Significant predictors for hepatotoxicity included older age, chronic alcohol drinking, repeated taking of medication for more than 8 h (staggered ingestion), long duration between ingestion and hospital visit, alcohol coingestion, abdominal pain symptoms, and acute kidney injury. Conclusions: Most cases of APAP overdose in Thailand appear to be young women with intentional ingestion. With prompt management, most patients (76.4%) did not develop significant hepatotoxicity; nevertheless, despite N-acetylcysteine therapy, hepatotoxicity including acute liver failure was observed in a small proportion of patients, particularly those with unintentional overdose and chronic alcohol drinking.